Cardiorenal syndrome and death risk in patients with heart failure or chronic kidney disease: an unmet cardiorenal need?. (14th October 2021) - Taveira Gomes, T; Santos Araujo, C; Valente, F; Bernardo, F; Seabra Carvalho, D; Bodegard, J; Gavina, C
Abstract: Introduction: Heart failure (HF) and chronic kidney disease (CKD) have interlinked pathophysiological pathways and patients having both conditions simultaneously are defined as having cardiorenal syndrome (CRS). Purpose: To estimate the risk of CRS in patients with initial presentation of HF (without prior CKD) or CKD (without prior HF) compared to mean age overall population in a real-world clinical setting. Also, to estimate the risk of all-cause death, cardiovascular (CV) death and non-fatal major CV events (MACE) in patients with HF, CKD and CRS compared to the mean-age overall population. Methods: Clinical database analysis of a single primary and secondary healthcare institution from 2008–2019. We defined 4 incident cohorts: Control - patients at age 75; HF - HF patients without prior CKD; CKD - CKD patients without prior HF; CRS - patients with HF and CKD. Patients were indexed at the date of first event and followed one year. We defined HF as either: i) Ejection Fraction (EF)≤40% and NT-proBNP≥200pg/mL (≥600pg/mL if atrial fibrillation (AF)) OR BNP≥100pg/mL (≥125pg/mL if AF); ii) EF>40% in the presence of structural cardiac abnormalities. We defined CKD as eGFR≤60mL/min using EPI-CKD formula. All definitions were constructed using laboratory-level data complemented with episode-level data. Hazard ratios (HR) and 95% confidence intervals were estimated using Cox regression models adjusted for age, sex, age-sex interaction, prior history of hypertension, myocardial infarction, stroke, peripheral artery disease and type 2 diabetes. Results: We identified 3973 patients with HF, 13990 with CKD, 6784 with CRS and 16182 controls. Patients were in general 75–77 years old. The majority were females and were well treated with CV risk reducing drugs (Table 1). All-cause death risk was 4.7 (4.1–5.2) for HF and 4.9 (4.5–5.4) for CKD. CV death risk was 8.6 (6.8–10.8) for HF and 8.7 (7.1–10.6) for CKD. Non-fatal MACE risk was 7.4 (6.3–8.7) for HF, 4.6 (4.0–5.3) for CKD, and 7.1 (6.1–8.3) for CRS. CRS was associated with the highest risks of all-cause and CV death when compared with the control group- 7.1 (6.4–7.9) and 13.7 (11.7–17.0), respectively (Figure 1). More than half of events occurred in the first 90 days of follow-up for all outcomes. Conclusions: Cardiorenal disease (HF or CKD) was associated with very high short-term risk (1 year) of developing CRS or death. Consecutively, patients with established CRS had the highest risk of dying. These results demonstrate serious cardiorenal risks in a real-world setting, supporting an urgent need for improved primary and secondary prevention of cardiorenal disease and cardiorenal syndrome. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): AstraZeneca Produtos Farmacêuticos, Lda.